Interpreting Plenoptic Images as Multi-View Sequences for Improved Compression - Ahmad, Waqas; Roger, Olsson; Sjöström, Mårten (Mid Sweden University, 2017)
The paper is written in the response to ICIP 2017, Grand challenge on plenoptic image compression. The input image format and compression rates set out by the competition are followed to estimate the results.

Tables and figures.

The dataset was originally published in DiVA and moved to SND in 2024.

The paper is written in the response to ICIP 2017, Grand challenge on plenoptic image compression. The input image format and compression rates set out by the competition are followed to estimate the results.

Tables and figures.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Interpreting Plenoptic Images as Multi-View Sequences for Improved Compression
Keywords: plenoptic; plenoptic; Light field; Light field; MV-HEVC; MV-HEVC; Computer and Information Sciences; Data- och informationsvetenskap (datateknik)